Low Phase Angle Is Correlated With Worse General Condition in Patients with Advanced Cancer. (2nd January 2019) - Miura, Tomofumi; Matsumoto, Yoshihisa; Kawaguchi, Takashi; Masuda, Yuto; Okizaki, Ayumi; Koga, Hiroko; Tagami, Keita; Watanabe, Yuki Sumazaki; Uehara, Yuko; Yamaguchi, Takuhiro; Morita, Tatsuya
Abstract: Objectives: Phase angle (PA) is a poor prognostic factor in patients with advanced cancer. This study aimed to identify possible correlations between PA and symptoms, quality of life, fluid retention, and laboratory data in cancer patients in palliative care settings. Methods: Individuals who visited the outpatient clinic or were admitted to the palliative care unit were eligible. Patients with a performance status of 4 and/or those unable to complete questionnaires were excluded. PA was evaluated using a bioanalyzer device. The correlation coefficient between PA and the variables of interest was analyzed. Results: A total of 102 patients were analyzed. PA was weakly correlated with age ( ρ = −0.22), performance status ( ρ = −0.30), functional well-being ( ρ = 0.20), anorexia/cachexia subscale ( ρ = 0.22), and Functional Assessment of Anorexia/Cachexia Therapy trial outcome index ( ρ = 0.26). PA was also correlated with fluid retention ( ρ = −0.34) and albumin ( ρ = 0.32), C-reactive protein ( ρ = −0.31), and hemoglobin ( ρ = 0.41) levels. Sub-analysis stratified according to sex revealed that males demonstrated the same results; however, female sex demonstrated a correlation between PA and social well-being ( ρ = −0.43). Conclusions: PA was correlated with physical condition, but not with psychological well-being.